PENGUATAN KEMAMPUAN LITERASI SISWA KELAS V SD NEGERI 15 PAREPARE - Abdul Rahman; Hastuty, Hastuty; Dollo, Asdar; Ahmad, Henra; Sari, Vernita; Asfa, Siti Maryam (Media Literasi Indonesia, 2025)
Literacy is an important aspect in basic education because it determines learning success at the next level. Literacy is not only limited to reading and writing, but also the ability to understand, process and utilize information. However, low motivation, limitations in utilizing reading materials and supporting learning environments are still obstacles. This service program is an effort to strengthen literacy skills among students at SD Negeri 15 Parepare which is carried out from August to December. This activity aims to strengthen students' literacy skills by creating learning media and mentoring. The media created are literacy trees, reading corners, and library improvements with the program name